Oxygen Evolution Nickel Hydroxide Electrodes in a Ni-MH Battery Prototype - Becker, María Daniela (2012)
The effect of cobalt in both alpha and beta phases on the oxygen evolution of nickel hydroxide was studied. The electrochemical properties of the oxygen evolution reaction on the positive nickel hydroxide electrodes were studied under conditions similar to those of a commercial Ni-MH battery. The presence of different kinds of defects in the structure of the active material was determined by XRD methods distorted and asymmetric reflections in the XRD patterns. Both the morphology of the active material and the additives influence the oxygen evolution potential and the electrochemical characteristics. The experimental results showed that the optimized prototype used in this work is suitable for evaluating several electrochemical parameters. It was shown that the electrode without cobalt exhibited the charging efficiency was 94% and those with cobalt exhibited a charging of 98%.